The Apoplastic Secretome of Trichoderma virens During Interaction With Maize Roots Shows an Inhibition of Plant Defence and Scavenging Oxidative Stress Secreted Proteins - Nogueira-Lopez, Guillermo; Greenwood, David R.; Middleditch, Martin; Winefield, Christopher; Eaton, Carla; Steyaert, Johanna M.; Mendoza-Mendoza, Artemio (Frontiers in Plant Science, 2018)
In Nature, almost every plant is colonised by fungi. Trichoderma virens is a biocontrol fungus which has the capacity to behave as an opportunistic plant endophyte. Even though many plants are colonised by this symbiont, the exact mechanisms by which Trichoderma masks its entrance into its plant host remain unknown, but likely involve the secretion of different families of proteins into the apoplast that may play crucial roles in the suppression of plant immune responses. In this study, we studied T. virens colonization of maize roots under hydroponic conditions, evidencing inter and intracellular colonization by the fungus and modifications in root morphology and colouration. Moreover, we show that upon host penetration, T. virens secretes into the apoplast an arsenal of proteins to facilitate inter- and intracellular colonisation of maize root tissues. Using a gel-free shotgun proteomics approach, 95 and 43 secretory proteins were identified from maize and T. virens, respectively. A reduction in the maize secretome (46%) was induced by T. virens, including two major groups, glycosyl hydrolases and peroxidases. Furthermore, T. virens secreted proteins were mainly involved in cell wall hydrolysis, scavenging of reactive oxygen species and secondary metabolism, as well as putative effector-like proteins. Levels of peroxidase activity were reduced in the inoculated roots, suggesting a strategy used by T. virens to manipulate host immune responses. The results provide an insight into the crosstalk in the apoplast which is essential to maintain the T. virens-plant interaction.